Formulation, Development, and Evaluation of Indomethacin Emulgel Using Pregelatinized Starch from Ipomoea batata Tubers (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The purpose of the present study was to develop and optimize the emulgel system for indomethacin (IND),using four types of gelling agents: Carbopol 934, HPMC K4M, xanthum gum, and pregelatinized Ipomoea batatastarch (PGIBS), which are dispersed in purified water with constant stirring at a moderate speed, then the pH wasadjusted to 6-6.5 using triethanolamine. Materials and Methods: The prepared emulgels were evaluated in termsof physical appearance, pH, spreadability, rheological study, viscosity, drug content determination, in vitro drugrelease, accelerated stability studies, and fitting of results into different kinetic equations was also carried out.Statistical Analysis Used: The Fourier transform infrared spectra of the IND and different polymers alone andin combination show the compatibility of the drug and excipients. Results: In vitro release study demonstrateddiffusion controlled release of IND from formulation up to 8 h. The formulations showed higher RÂ² values forzero order plots indicating that drug release followed zero order kinetics a. The accelerated stability studieswere performed according to ICH guidelines for 3 months, and the results were found to be stable in varyingtemperature. All the prepared emulgels showed acceptable physical properties concerning color, homogeneity,consistency, spreadability, pH value, and with higher drug release than conventional gel. Conclusion: Theoptimized formulations were found to be C4, H4, G4, and I4 containing a lower concentration of light castoroil and a higher concentration of emulsifiers. In the case of all evaluation parameters PGIBS and castor oilbasedformulation, i.e., I4 showed better properties. So, as a general conclusion, it was suggested that the INDemulgel formulation prepared with PGIBS having the oil phase concentration in its low level and emulsifyingagent concentration in its high level was the formula of choice. The results demonstrate that the release of the drugis dependent on the viscosity of the polymer used.